Practice of diagnostic hysteroscopy after myomectomy in the prevention of intrauterine adhesions: experience of Ouakam military hospital (Dakar, Senegal) - Faye Dieme, Marie Edouard; Niang, Mouhamadou Mansour; Gassama, Omar; Diouf, Abdoul Aziz; Coulibaly, Marietou Thiam; Diouf, Alassane; Moreau, Jean Charles (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Surgical treatment of myomas may be the cause of some complications, including intrauterine adhesions. The objective of the study was to evaluate the incidence of intrauterine adhesions in patients who underwent myomectomy by laparotomy or hysteroscopic resection. Methods: We carried out a prospective single center study from August 1st 2016 to May 31st 2017 in the gynaecological and obstetrical department of Ouakam the Military Hospital (Senegal). We included patients who underwent myomectomy by laparotomy with opening of the uterine cavity or myomectomy by hysteroscopy. A diagnostic hysteroscopy was performed to search post-operative intrauterine adhesions. For each patient, we studied the socio-demographic aspects, the surgical approach, the delay of diagnostic hysteroscopy, the appearance of uterine cavity and the tolerance of hysteroscopy. Results: 54 patients underwent the diagnostic hysteroscopy. The mean age was 36 years old. The main indication of myomectomy was menorrhagia. 37 patients underwent myomectomy by laparotomy and 17 by hysteroscopy. Each case was followed by a post-operative diagnostic hysteroscopy with a mean delay time of 58 days. We found post-operative intrauterine adhesions in 7 patients (5 in the laparotomy group and 2 in hysteroscopy group). Conclusions: Early diagnostic hysteroscopy after myomectomy should be done in our context to reduce post-operative intrauterine adhesions and preserve the patient’s fertility.